2011
DOI: 10.1007/s12560-011-9071-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Norovirus Infection in Children and Adults with Acute Gastroenteritis, Tehran, Iran, 2008–2009

Abstract: Noroviruses are one of important agents that cause acute viral gastroenteritis worldwide. These viruses are belonging to Caliciviridae family and are genetically diverse. To date, there is no valuable data about prevalence of norovirus infection and the dominant genogroup/genotype among Iranian population. The objective of this study was to determine the frequency of norovirus infection in Iranian patients with gastroenteritis referred to three hospitals of Tehran and to specify the dominant genogroup/genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
2
16
0
1
Order By: Relevance
“…Nadji et al in 2010 performed a small scale study on 47 stool samples of patients with gastroenteritis and reported that Norovirus and Sapovirus are found in 21.3% and 2.1% of samples (24). Our previous work has demonstrated that two genotypes (GI and GII) of Norovirus are involved in 9.8% of acute gastroenteritis cases (4). In other study among Iranian patients with acute gastroenteritis, we demonstrated that Sapoviruses could be responsible for 11.9% of acute gastroenteritis cases (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nadji et al in 2010 performed a small scale study on 47 stool samples of patients with gastroenteritis and reported that Norovirus and Sapovirus are found in 21.3% and 2.1% of samples (24). Our previous work has demonstrated that two genotypes (GI and GII) of Norovirus are involved in 9.8% of acute gastroenteritis cases (4). In other study among Iranian patients with acute gastroenteritis, we demonstrated that Sapoviruses could be responsible for 11.9% of acute gastroenteritis cases (2).…”
Section: Discussionmentioning
confidence: 99%
“…HBoV DNA was detected in extracted samples by polymerase chain reaction (PCR) amplification of a 354 bp of noncapsid protein 1 (NP1) gene using primers 188F and 542R as reported previously (5). In addition, all samples were also subjected to a nested PCR as described by Kapoor et al, to amplify a 455 bp of nonstructural 1 (NS1) gene (3). The BigDye Terminator v3.1 cycle sequencing kit (Applied Biosystems, Foster City, CA, USA) was employed for sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La mayoría de las publicaciones se refieren a niños menores de cinco años y solo unas pocas proponen evaluar la presencia de norovirus en personas de diferentes edades, lo que indica que la inmunidad a largo plazo está ausente (6,13,30,31 Los resultados del presente estudio son similares a los de Romani, et al, quienes analizaron 293 pacientes provenientes de Teherán (Irán), con un promedio de edad de 11,72 años (rango: 1 mes a 85 años) y una prevalencia de norovirus de 9,8 % (31). Se encontró que existía una relación estadísticamente significativa (p<0,05) para la edad, dado que el virus se detectó con mayor frecuencia en niños entre uno y cuatro años de edad (11 de 16 muestras positivas).…”
Section: Discussionunclassified
“…The high prevalence of gastroenteritis caused by Norovirus in these countries can be due to various factors different from the middle east. For example, the consumption of raw marine products such as oysters is one of the main causes of Norovirus spread in developed countries (22); however, this dietary pattern is rare in middle eastern countries (including Iran) (13). Therefore, the prevalence of Norovirus in these countries is less.…”
Section: Discussionmentioning
confidence: 99%